2014
DOI: 10.5114/pwki.2014.43514
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of inflammatory markers in non-dipper hypertension vs. dipper hypertension and in normotensive individuals: uric acid, C-reactive protein and red blood cell distribution width readings

Abstract: AimIn this study, we investigated the relationship of increased inflammatory parameters (C-reactive protein – CRP), oxidative stress markers (serum uric acid – SUA) and red blood cell distribution width (RDW) with non-dipper hypertension (NDHT).Material and methodsAmong the individuals who presented to the cardiology clinic, 40 patients (32.5% male, 67.5% female; mean age: 54.4 ±7.1) who had hypertension and were diagnosed with NDHT through ambulatory blood pressure monitoring, 40 age- and sex-matched dipper h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 29 publications
(27 reference statements)
1
16
0
1
Order By: Relevance
“…Our results showed increased inflammation and oxidative stress, are significantly higher in the non-dipper hypertension, which is consistent with the previous study [21]. It was reported that the risk for adverse cardiovascular events in human peaks in the morning, possibly due to the effects of the endogenous circadian system on cardiovascular risk factors, or the occurrence of mental stress.…”
Section: Discussionsupporting
confidence: 93%
“…Our results showed increased inflammation and oxidative stress, are significantly higher in the non-dipper hypertension, which is consistent with the previous study [21]. It was reported that the risk for adverse cardiovascular events in human peaks in the morning, possibly due to the effects of the endogenous circadian system on cardiovascular risk factors, or the occurrence of mental stress.…”
Section: Discussionsupporting
confidence: 93%
“…A nocturnal non-dipping pattern is a situation accompanied by inflammation21) and endothelial dysfunction 17)22). The clinical relevance of a non-dipping status in HT patients lies in its proven association with more severe target organ damage and increased risk for cardiovascular events 23)24).…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Also, elevated serum uric acid (SUA) concentrations have been observed in HT, cardiovascular diseases, chronic kidney diseases and metabolic syndrome related with inflammatory status. 5,6 In this study, serum NLR, CRP and uric acid levels of patients with CSU were measured and it was investigated whether or not these parameters have an association with clinical disease activity.…”
mentioning
confidence: 99%